Information System of Meeting - Khairul Anwar Hafizd; Fathurrahmani; Herpendi (Sean Institute, 2023)
The intense coordination carried out by the Politala management often results in conflicts with other scheduled or urgent activities. The occurrence of this conflict resulted in the absence of one or several meeting members which resulted in less than the expected meeting results. In addition, in the absence of meeting scheduling, it is not uncommon for participants to be absent due to forgetting. This study aims to develop a mobile-based application to make it easier for the leader or chairman of the activity committee to schedule meeting activities for members. The information on the scheduled meeting can be accessed by the participants who have been designated as invitees. During meeting activities, meeting minutes can take minutes in the application and highlight important points by including the deadline date and addressed to the desired meeting participants so that the target is clear. The progress of activities charged by meeting participants can be seen in real time by the chairman of the meeting to the leadership. This research was conducted using the prototype method and data collection by observation and interview methods to produce an E-Meet application.